Multiple connections between Amazonia and Atlantic Forest shaped the phylogenetic and morphological diversity of Chiasmocleis Mehely, 1904 (Anura: Microhylidae: Gastrophryninae) - de Sá, Rafael O.; Tonini, João Filipe Riva; van Huss, Hannah; Long, Alex; Cuddy, Travis; Forlani, Mauricio C.; Peloso, Pedro L.V.; Zaher, Hussam; Haddad, Célio F.B. [UNESP] (Elsevier, 2019)
Chiasmocleis is the most species-rich genus of Neotropical microhylids. Herein, we provide the first comprehensive multilocus phylogeny for the genus, including all but 3 of the 34 recognized species and multiple individuals per species. We discuss cryptic speciation, species discovery, patterns of morphological evolution, and provide a historical biogeographic analysis to account for the current distribution of the genus. Diversification of Chiasmocleis from other New World microhylids began during the Eocene, app. 40 mya, in forested areas, and current diversity seems to be a product of recurrent connections between the Atlantic Forest and Amazonia. Small-sized species evolved independently three times in Chiasmocleis. Furthermore, the extremely small-bodied (i.e. miniaturized) species with associated loss of digits, phalanges, and pectoral girdle cartilages evolved only once and are restricted to Amazonia. Using the phylogeny, we recognized three subgenera within Chiasmocleis: Chiasmocleis Méhely, 1904, Relictus subg. nov., and Syncope Walker, 1973. The recognition of the subgenus Syncope informs future research on patterns of miniaturization in the genus, and the subgenus Relictus highlights isolation of an endemic and species-poor lineage to the Atlantic Forest, early (about 40 mya) in the history of Chiasmocleis.
Keywords: Biogeography; Chiasmocleis; Miniaturization; Morphology; Phylogeny; Species discovery